Synthesis of novel 3/5(3, 5)-(di)nitropaeonol hydrazone derivatives as nematicidal agents. Issue 1 (2nd January 2022) - Chen, Gen-Qiang; Zhu, Li-Na; Yang, Jin-Ming; Zhang, Song; Li, Yuan-Hao; Guo, Xiao-Long; Sun, Di; He, Jia-Xuan; Tian, Yue-E; Liu, Sheng-Ming; Jiang, Jia; Huang, Xiao-Bo; et al.
Abstract: Eighteen novel 3/5(3, 5)-(di)nitropaeonol hydrazone derivatives were prepared, and their structures well characterized by 1 H NMR, HRMS, and mp. Due to the steric hindrance, the substituents on the C = N double bond of all hydrazine compounds (except E/Z = 4/1 for IV-1g, IV-1l, IV-2b, and E/Z = 3/2 for IV-1n, IV-3a ) adopted E configuration. Among all compounds, four compounds 2, 4, IV-1j, and IV-1n exhibited potent nematicidal activity than their precursor paeonol, especially 5-nitropaeonol (2 ) and 3, 5-dinitropaeonol (4 ) displayed the most potent nematicidal activity Heterodera glycines in vivo with LC50 values of 32.3307 and 36.7074 mg/L, respectively. Graphical abstract: UF0001